Perspektif Ibnu Khaldun tentang Ilmu dan Pendidikan dalam Peradaban Islam - Nur Azizah Khoirun Nisa; Syafriya Indayani; Zhafira Atsari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study explores Ibn Khaldun’s views on knowledge and education within the broader framework of Islamic civilization, as well as their relevance to contemporary Islamic education. It is motivated by various challenges in modern Islamic education, such as the decline of moral values, the fragmentation of knowledge, and the diminishing role of spirituality in learning processes. The aim of this research is to examine Ibn Khaldun’s educational thought and assess how it can contribute to solving current educational problems. The study adopts a qualitative approach using library research, with Ibn Khaldun’s Muqaddimah as the main source, supported by relevant books and journal articles. The findings show that Ibn Khaldun promotes a holistic view of education that integrates intellectual, moral, and social dimensions. He also highlights gradual instruction (tadrij), repetition (takrir), and the importance of considering learners’ psychological conditions in the teaching process. In addition, education is closely connected to social cohesion (‘asabiyyah) and the development of civilization (‘umran). The study concludes that Ibn Khaldun’s educational ideas remain highly relevant today and can offer valuable insights for rethinking and improving Islamic education in the modern era.